Dementia incidence and predictors in cerebral amyloid angiopathy patients without intracerebral hemorrhage. Issue 2 (February 2018) - Xiong, Li; Boulouis, Gregoire; Charidimou, Andreas; Roongpiboonsopit, Duangnapa; Jessel, Michael J; Pasi, Marco; Reijmer, Yael D; Fotiadis, Panagiotis; Ayres, Alison; Merrill, Emily; Schwab, Kristin; Blacker, Deborah; et al.
Cerebral amyloid angiopathy (CAA) is a common cause of cognitive impairment in older individuals. This study aimed to investigate predictors of dementia in CAA patients without intracerebral hemorrhage (ICH). A total of 158 non-demented patients from the Stroke Service or the Memory Clinic who met the modified Boston Criteria for probable CAA were included. At baseline, neuroimaging markers, including lobar microbleeds (cerebral microbleeds (CMBs)), white matter hyperintensities (WMH), cortical superficial siderosis (cSS), magnetic resonance imaging (MRI)-visible centrum semiovale perivascular spaces (CSO-PVS), lacunes, and medial temporal atrophy (MTA) were assessed. The overall burden of small vessel disease (SVD) for CAA was calculated by a cumulative score based on CMB number, WMH severity, cSS presence and extent and CSO-PVS severity. The estimated cumulative dementia incidence at 1 year was 14% (95% confidence interval (CI): 5%–23%), and 5 years 73% (95% CI: 55%, 84%). Age (hazard ratio (HR) 1.05 per year, 95% CI: 1.01–1.08, p = 0.007), presence of MCI status (HR 3.40, 95% CI: 1.97–6.92, p < 0.001), MTA (HR 1.71 per point, 95% CI: 1.26–2.32, p = 0.001), and SVD score (HR 1.23 per point, 95% CI: 1.20–1.48, p = 0.030) at baseline were independent predictors for dementia conversion in these patients. Cognitive deterioration of CAA patients appears attributable to cumulative changes, from both vasculopathic and neurodegenerative lesions.